If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2.9)(7) = (4)(X) Multiply 2.9 * 7 20.3 = (4)(X) Solving 20.3 = 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 20.3 + -4X = 4X + -4X Combine like terms: 4X + -4X = 0 20.3 + -4X = 0 Add '-20.3' to each side of the equation. 20.3 + -20.3 + -4X = 0 + -20.3 Combine like terms: 20.3 + -20.3 = 0.0 0.0 + -4X = 0 + -20.3 -4X = 0 + -20.3 Combine like terms: 0 + -20.3 = -20.3 -4X = -20.3 Divide each side by '-4'. X = 5.075 Simplifying X = 5.075
| (10+x)(10+(x+5))=300 | | xsquared+12=373 | | h=-16t^2+39t+20 | | 10y=5x+4 | | xsquared-32=81 | | 3a+5b=8 | | X-2(x+7)=4(2x-1) | | 7ysqared=112 | | 100+x=12x+1 | | 3squared+24=88 | | 6+18y= | | 12(x+8)=10x+16 | | 2x-4n-8=0 | | 8x+5=10x-5 | | 0.66x-5=2x | | 3(x-4)=-4+44 | | 15+3n=27 | | -6=-4-2x | | -8x(x+1)=4(x-11) | | 4x+1=5j-1 | | y=x^2+60x-300 | | 4(3+3x)-2=70 | | x+(x+5)=69 | | 22x=25x-6 | | 6(2n-1)=2(5n-3)+4n | | 9y+1=8y-2 | | (u-7)(u+1)= | | 3(a-5)+7=-2 | | 3x^2-21x-36=0 | | -3(6-2t)=-48 | | 8z^2+20z-49=0 | | 5x+15-2x=25+3x-10 |